Barrelyzer: Design and Implementation of a Low-Cost Tank Barrel Inspection System - (:unkn) unknown (Springer Nature Switzerland, 2024)
Maintaining confined spaces such as 10 cm barrels and pipes is a challenging task to perform without the use of intelligent systems. However, these devices are high-priced and require special training for the operators. Hence, the present paper proposes ...
Keywords: Inspección de barriles; Bajo costo